2005
DOI: 10.1111/j.1365-2796.2005.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Severity of coronary artery stenosis is associated with a polymorphism in the CXCL16/SR‐PSOX gene

Abstract: Abstract. Lundberg GA, Kellin A, Samnegård A, Lundman P, Tornvall P, Dimmeler S, Zeiher AM, Hamsten A, Hansson GK, Eriksson P (Ö rebro University, Ö rebro and Karolinska Institute, Stockholm, Sweden; and University of Frankfurt, Frankfurt, Germany). Severity of coronary artery stenosis is associated with a polymorphism in the CXCL16/SR-PSOX gene. J Intern Med 2005; 257: 415-422.Objective. Enhanced expression of CXCL16 has been demonstrated in atherosclerotic plaques and several properties have been attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 29 publications
1
40
0
2
Order By: Relevance
“…All patients included in this study had an advanced phenotype of carotid atherosclerosis, with a high degree of carotid artery stenosis ( 70%). Therefore, our results are in agreement with those of Lundberg et al 16) . However, since this study had limited statistical power for the observed association, we consider our findings to be preliminary.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…All patients included in this study had an advanced phenotype of carotid atherosclerosis, with a high degree of carotid artery stenosis ( 70%). Therefore, our results are in agreement with those of Lundberg et al 16) . However, since this study had limited statistical power for the observed association, we consider our findings to be preliminary.…”
Section: Discussionsupporting
confidence: 83%
“…The role of CXCL16 in the onset of cardiovascular pathology was first documented when the levels of its soluble form were found to be positively and independently associated with acute coronary syndrome 27) . The A181V polymorphism was subsequently investigated in a few different populations in association with coronary artery disease [16][17][18] , but not carotid atherosclerosis. In one of these studies, a significant association between the V181V genotype and a high degree of coronary artery stenosis was found in Caucasian CAD patients 16) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations